Development of suitable technology for the canning of smoked Mediterranean mussels (Mytilus galloprovincialis) in tomato sauce - KYRIAZI-PAPADOPOULOU (Α. ΚΥΡΙΑΖΗ -ΠΑΠΑΔΟΠΟΥΛΟΥ), A.; VARELTZIS (Κ. ΒΑΡΕΛΤΖΗΣ), K. (Journal of the Hellenic Veterinary Medical Society, 2018)
The following procedure for the canning of smoked Mediterranean mussels (Mytilus galloprovincialis) was developed and studied. Mussels from the mussel culture of the East Cost of Thermaikos Bay were washed in running water and steamed at 80 °C for 10 min, in order to remove or open the shells. The mussel meat was salted in brine with 4% sodium chloride for 15 min, in a mussel /brine ratio 1:2, dried at 60-65°C for 13 min and smoked at 65-80°C for 17 min. The smoked mussel meat was placed in cans and filled with tomato sauce, in a ratio 32% mussel to 60% sauce. After the sealing cans were sterilized at 110°C for 21 min, to insure Fo value=4,l min. Chilling with cold water and storage in environmental conditions followed. The results demonstrated that the thermal processing safeguarded the microbiological stability of the canned mussels, due to the smoke components, since no swelling of cans was observed after incubation at 37°C for 7 days and during storage at ambient conditions for 15 months. The results of the sensory evaluation showed that the sauce was preserved without deterioration for 15 months. Also, the mussels' tenderness and their total acceptability lasted for 15 months . But the mussels displayed a grainy texture on chewing after 13 months preservation. Therefore, the procedure, which was developed for the canning of smoked mussels meat in tomato sauce, can provide an acceptable product for 13 months.